Four-year record of mercury wet deposition in one typical industrial city in southwest China. (October 2016) - Qin, Caiqing; Wang, Yongmin; Peng, Yulong; Wang, Dingyong
Abstract: During the period from December 2010 to November 2014, long-term monitoring of Hg wet deposition was conducted at three sites in Chongqing. The four-year volume-weighted mean concentrations (VWC) of total mercury (THg) and methylmercury (MeHg) in precipitation were 34.25 ng L −1 and 0.48 ng L −1, respectively. The average annual wet deposition fluxes were 37.83 ± 11.53 μg m −2  yr −1 for THg and 0.61 ± 0.19 μg m −2  yr −1 for MeHg. Besides, the average proportion of MeHg in THg was 1.41%. These data were well ahead of values observed in most of other areas. The annual VWC of Hg rose remarkably in 2012 and then reached a plateau or climbed mildly in the following 2 years, while its annual wet deposition fluxes saw an upward trend throughout the whole period. In addition, the high figures of Hg concentration were generally found in the non-monsoon seasons, but its elevated wet deposition fluxes normally appeared in the rainy seasons. These characteristics of inter-annual and seasonal changes for VWC and fluxes were observed at every sampling site in this study as well. Besides, there were significantly spatial distributions for VWC and fluxes of THg in the descending order of the downtown (NA), the suburban (BB) and the controlled site (JY). While for MeHg, BB had the largest values, followed by NA and JY. So apart from THg load, the formation of MeHg was influenced by other factors in Chongqing, like the concentration of reactive mercury (RHg) in precipitation. Additionally, particulate bound mercury (PHg) is the dominant form among various Hg species, and atmospheric Hg is effectively eliminated during the initial period of the rain event and the below-cloud scavenging is the predominant mechanism contributing Hg to precipitation. Highlights: Atmospheric Hg is primarily associated with local emission sources and long-range transport. The below-cloud scavenging is the predominant mechanism contributing Hg to precipitation. The formation of MeHg in atmosphere and methylation are influenced by the concentration of RHg, besides the local THg load.